(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to find out how the coordination among regional apparatus organizations in the preparation of AMDAL with smelter companies in Bantaeng Regency. The research method used a qualitative research method. The number of informants in this study was 9 people. Data collection techniques used observation, interviews and documentation. The results of this study showed that the unity of action so far in the process of coordination of employment and industry with the environmental service and PT. Huady Nickel Alloy Indonesia had not run well in accordance with what was expected because there were still many complaints from the public, the communication side which was a weakness of the employment and industry department with the environmental service and PT. Huady Nickel Alloy Indonesia because this day there were still many people who complaint about the waste from the nickel, in terms of the division of labor employment and industry with the environmental department and PT. Huady Nickel Alloy Indonesia there was still unconsciousness in each member, and the discipline in coordinating employment and industry services with the environmental department and PT. Huady Nickel Alloy Indonesia had coordinated in accordance with applicable regulations.